Lichen Planus Pemphigoides Induced by Enalapril: A Case Report and a Review of Literature - Woranit Onprasert; Kumutnart Chanprapaph (Karger Publishers, 2017)
Lichen planus pemphigoides (LPP) is a rare autoimmune bullous dermatosis. The clinical presentation of LPP may mimic bullous pemphigoid making the diagnosis difficult. A thorough clinical, histopathological, and immunological evaluation is essential for the diagnosis of LPP. The etiology is largely idiopathic; however, there are several case reports of drug-induced LPP. We report an 81-year-old Thai woman with underlying hypertension and type 2 diabetes mellitus who presented with a 4-week history of multiple tense bullae initially on the hands and feet that subsequently expanded to the trunk and face. Enalapril was commenced to control hypertension. The histopathology and direct immunofluorescence were compatible with LPP. Circulating anti-basement antibodies BP180 was also positive. The patient was treated with topical corticosteroid with a modest effect. Enalapril was discontinued and complete resolution of LPP occurred within 12 weeks. There was no recurrence after a 1-year follow-up period. To the best of our knowledge, we present the first case of enalapril-induced LPP. Early recognition and prompt discontinuation of the culprit drug allow resolution of the disease. Medication given for LPP alone, without cessation of the offending drug, may not change the course of this condition.